Geopolymer Mortars from Tuff Waste: A Circular Approach - Muradyan, Nelli; Arzumanyan, Arusyak; Kalantaryan, Marine; Khachatryan, Kristina; Zendri, Elisabetta; Arzumanyan, Avetik (Civil Engineering Journal, 2025)
This study explores the potential use of volcanic tuff mining waste in geopolymer mortar formulations, aiming to enhance recycling and promote sustainable construction. Two filler-to-binder ratios (70/30 and 65/35) were developed using a geopolymer binder composed of tuff waste, dolomite powder, and sodium silicate. The mortars were subjected to heat treatments at 200, 350, 500, and 650°C for 8.5 hours. Compared to natural tuff (reference sample), water absorption decreased from 16.8% to 7.7%, with the lowest absorption observed in the 65/35 composition. Flexural strengths increased by 0.97% to 117.1%, and compressive strengths improved by 17.8% to 97.1%, reaching their maximum at 500°C; at 650°C, strengths declined due to water evaporation, shrinkage, and microcrack formation. Softening coefficients increased by over 10%, indicating enhanced resistance to water-induced softening. The study demonstrates that incorporating dolomite powder improves water resistance, while tuff waste serves effectively as both filler and binder component. Moreover, geopolymer mortars produce significantly lower CO₂ emissions (0.133 t/m³) compared to ordinary Portland cement mortars (0.415 t/m³), highlighting their environmental advantage. These results underscore the potential of tuff-based geopolymer mortars for sustainable construction applications.